The digital labour challenge: work in the age of new media - White, Aidan (Geneva, 2012)
"This sectoral working paper outlines how technology has been the driver of change in the media and entertainment sector, in the habits of consumers, and in the labour market. The proliferation of new technologies has eliminated many traditional media and entertainment jobs, but there has been expanded consumption of media products worldwide and a growth in employment in new areas of media and entertainment. There have been significant changes in work organization – particularly in content creation. This has fuelled demands for flexible work and for people who can provide creative input across a range of media.